Effect of temperature on the formation and degradation of polycyclic aromatic hydrocarbons - Pakpahan, E.N.; Isa, M.H.; Kutty, S.R.M.; Malakahmad, A. (2009)
Polyaromatic hydrocarbons (PAHs) are a class of aromatic hydrocarbon compounds which are catagorised as pollutants with carcinogens, and mutagenic characteristics. Scientifically, incomplete combustion and petroleum compounds emission were proven as a major source of PAHs. Thermal degradation of PAHs is one of the methods to destroy the pollutants as well as their hazardous by-products. During thermal treatment process, formation and/or degradation of PAHs is related to their chemical structural stability and rate of degradation. Summarized, PAHs with four or more rings are formed at low-temperature thermal treatment, and only the ones with less than 4 rings are degraded. High-temperature thermal treatment generally forms PAHs with 4 rings or less and degrades 5 rings or more. Due to environmental and human health considerations, thermal treatment of PAHs should be designed to completely degrade or destroy the pollutants as well as their hazardous byproducts. High-temperature thermal treatment and liquid extraction are effective in the treatment of PAHs, but expensive. A cheap alternative treatment method such as optimization of low temperature treatment perhaps combined with catalysis needs to be developed in order to reduce PAHs formation and increase their degradation simultaneously.